Past agricultural land use affects multiple facets of ungulate antipredator behavior. (5th July 2021) - Bartel, Savannah L; Orrock, John L
Abstract: Antipredator behavior affects prey fitness, prey demography, and the strength of ecological interactions. Although predator-prey interactions increasingly occur in habitats that experience multiple forms of human-generated disturbance, it is unclear how different forms of disturbance might affect antipredator behavior. Fire is a contemporary disturbance that has dramatic effects on terrestrial habitats. Such habitats may have also experienced past disturbances, like agricultural land use, that leave lasting legacies on habitat structure (e.g., overstory and understory composition). It is unclear how these past and present disturbances affect the use of different antipredator behaviors, like temporal avoidance and vigilance. We examined whether variation in disturbance regimes generates differences in ungulate antipredator behavior by using cameras to measure white-tailed deer vigilance and activity time across 24 longleaf pine woodlands that vary in past land use and contemporary fire regime. Regardless of land-use history, woodlands with high fire frequencies had 4 times less vegetation cover than low-fire woodlands, generating riskier habitats for deer; however, deer responded to fire with different antipredator strategies depending on land-use history. In nonagricultural woodlands, fire affected deer activity time such that activity was nocturnal in low-fire woodlands and crepuscular in high-fire woodlands. In post-agricultural woodlands, fire affected vigilance and not activity time such that deer were more vigilant in high-fire woodlands than in low-fire woodlands. These results suggest that ungulate antipredator behavior may vary spatially depending on past land use and contemporary fire regime, and such disturbances may generate "landscapes of fear" that persist for decades after agricultural use. Abstract : Animals exhibit a diverse suite of antipredator behaviors to avoid predators. However, it is unclear if changes in habitats caused by both past and present human activities affect which antipredator behaviors animals employ. We found that past human activities (agricultural land use over 60 years ago) and contemporary human activities (prescribed burns) interacted to produce characteristic shifts in whether deer used vigilance or changes in activity timing as a primary antipredator behavior.